2016
DOI: 10.1089/chi.2014.0119
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Hospital-Based Multidisciplinary Pediatric Weight Management Program: Two-Year Outcomes of PHIT Kids

Abstract: Children maintained treatment gains achieved during a 24-week family-based behavioral weight management program at 2-year follow-up. Although these findings suggest that gains are sustainable, further research is needed to understand how these long-term changes impact child health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
1
31
0
1
Order By: Relevance
“…The attenuation and confounding of very high BMIz values could be particularly problematic in longitudinal studies that focus on children with obesity (8,2628,32). As these children age during follow-up, the extent of the compression of very high BMIz values will vary based on the values of L and S in the growth charts.…”
Section: Discussionmentioning
confidence: 99%
“…The attenuation and confounding of very high BMIz values could be particularly problematic in longitudinal studies that focus on children with obesity (8,2628,32). As these children age during follow-up, the extent of the compression of very high BMIz values will vary based on the values of L and S in the growth charts.…”
Section: Discussionmentioning
confidence: 99%
“…Although the report for the CDC growth charts (Kuczmarski et al, 2002) cautioned about extrapolating outside the 3rd and 97th percentiles of BMI, BMI z remains widely used in studies that include large numbers of children with very high BMIs (Hampl et al, 2016; Kreier et al, 2013; McCormick et al, 2014; Smego et al, 2017; Wang et al, 2015). We have shown that, among children with severe obesity, BMI z levels are only weakly associated with other measures of body size (Freedman et al, 2017a) and the current results highlight the drawbacks of attempting to assess longitudinal BMI z changes.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapolated z -scores based on the CDC growth charts are widely used among children who have very high BMIs (Baughcum et al, 2015; Hampl et al, 2016; Kreier et al, 2013; Smego et al, 2017; Wang et al, 2015). However, BMI z values for extremely high BMIs can differ substantially from the empirical estimates (Flegal et al, 2009), have an effective upper limit (Woo, 2009) and are strongly influenced by sex and age.…”
Section: Discussionmentioning
confidence: 99%
“…However, BMI z ‐scores have been shown to be an inadequate and possibly biased measure of adiposity in children with severe obesity because a wide range of high BMI values corresponds to a relatively narrow range of BMI z ‐scores in an age‐dependent way . Despite this well‐documented shortcoming, BMI z ‐scores are still widely used to evaluate the response of obesity treatment in children with severe obesity . The BMI expressed as a percentage of a particular BMI cut‐off has been proposed as a more appropriate outcome parameter than BMI z ‐score in children with obesity.…”
Section: Introductionmentioning
confidence: 99%